2010
DOI: 10.1152/ajpregu.00082.2010
|View full text |Cite
|
Sign up to set email alerts
|

Increased renal α-epithelial sodium channel (ENAC) protein and increased ENAC activity in normal pregnancy

Abstract: West C, Zhang Z, Ecker G, Masilamani SM. Increased renal ␣-epithelial sodium channel (ENAC) protein and increased ENAC activity in normal pregnancy. Am J Physiol Regul Integr Comp Physiol 299: R1326 -R1332, 2010. First published August 4, 2010 doi:10.1152/ajpregu.00082.2010.-Pregnancy-mediated sodium (Na) retention is required to provide an increase in plasma volume for the growing fetus. The mechanisms responsible for this Na retention are not clear. We first used a targeted proteomics approach and found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
30
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 28 publications
6
30
1
Order By: Relevance
“…We found no change in renal cortical NCC (an aldosterone responsive sodium transporter in the distal tubule) with NIF-induced chronic vasodilation in the present study, although Wang et al did report increased NCC using a much higher dose of NIF (37). However, in normal pregnancy, we also observed that cortical NCC was unchanged (38); thus, the chronic systemic vasodilation in virgin female rats in the present study recapitulates the changes seen in normal pregnancy (24,38). The renal sodium retention of normal pregnancy is accompanied by early and sustained activation of the RAAS (5, 17, 34), a physiological response to an "underfill" signal.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…We found no change in renal cortical NCC (an aldosterone responsive sodium transporter in the distal tubule) with NIF-induced chronic vasodilation in the present study, although Wang et al did report increased NCC using a much higher dose of NIF (37). However, in normal pregnancy, we also observed that cortical NCC was unchanged (38); thus, the chronic systemic vasodilation in virgin female rats in the present study recapitulates the changes seen in normal pregnancy (24,38). The renal sodium retention of normal pregnancy is accompanied by early and sustained activation of the RAAS (5, 17, 34), a physiological response to an "underfill" signal.…”
Section: Discussioncontrasting
confidence: 83%
“…The main novel findings of this study are: 1) the apical sodium transporter profile of the distal nephron with chronic NIF-induced vasodilation is similar to the previously defined profile in pregnancy (38), with a selective increase in ␣-ENaC abundance in the medulla. 2).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Thus, ENaC appears to be a central element in Na + regulation in pregnancy. Although its transcript regulation is mediated via aldosterone,30 further activating modifications are due to protein‐cleaving conditions.…”
Section: Discussionmentioning
confidence: 99%